Recycle Waste Glass for Thermal Insulator - Agus Setyo Budi; Sujito Sujito (Jurnal ILMU DASAR, 2011)
Series of ceramics from recycle waste glass and mica powder have successfully been made and their physical properties of these glasses which include density, bulk modulus, volume expansion and compressive strength have been determined. Comparison of their physical specification to the conventional insulators has also been made. The results show that these ceramics exhibit reasonable mechanical, thermal and physical properties to be a potential thermal insulator.